Virus Infection of the Brain: Lessons from Drosophila for Illuminating Virus Disease and Nervous System Function. - Eleftherianos, I.; Tafesh-Edwards, G. (Neuroscience, 2022)
Recent studies using genomic and functional approaches in the fruit fly Drosophila melanogaster have revealed the effects of viral infection on nervous system homeostasis. An established connection between viral infection and brain function is critical due to its significant contribution to several areas of biomedical research, particularly the molecular pathogenesis of neurotropic viruses, the neurobiology of viral disease, and understanding the genetic basis and pathophysiology of viral tropism.